PERAN ROA SEBAGAI PEMEDIASI CAR, NPL DAN LDR BANK PEMBANGUNAN DAERAH DI INDONESIA - DEWI FADILA; YULIANI . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
This study aimed to analyze the effect of Capital Adequacy Ratio on Loan to Deposit Ratio, the role of Return on Assets as a mediating effect Capital Adequacy Ratio on Loan to Deposit Ratio, the effect of Non Performing Loanon Loan to Deposit Ratio, the role of Return on Assets as a mediating effect Non Performing Loanon Loan to Deposit Ratio. This study was called as a population study because the study sample was Regional Development Bank all over Indonesia as many as 26 banks. The observations period was 2009-2013. Data analysis was path analysis. The research findings were Capital Adequacy Ratio have significant negative effect on Loan to Deposit Ratio, Return on Assets as a partial mediating had an effect on relationship between Capital Adequacy Ratio and Loan to Deposit Ratio, Non Performing Loans did not have significant effect on Loan to Deposit Ratio, Return on Assets did not havemediating effect on relationship between Non Performing Loan and Loan to Deposit Ratio, Return on Assets have positive significant effect on Loan to Deposit Ratio.